Aktifitas Museum Deli Serdang Selama Masa Pandemi dalam Menunjang Edukasi Wisata di Kabupaten Deli Serdang - Muhammad Novriansyah Lubis; Surya Aymanda Nababan (Universitas Islam Sumatera Utara, 2021)
The purpose of this study was to see how the Deli Serdang Museum was active during the pandemic. By conducting online-based activities, the Deli Medium Museum provides tourism education to the Deli Serdang community. The Deli Serdang Museum provides something new during the pandemic in providing services to the community, by using social media the public can enjoy the tourism education provided by the Deli Serdang Museum online from home. This writing uses a descriptive qualitative method by conducting observations, interviews and literature studies.